An autoethnography of becoming a better English user: “I Learn while I Teach” - Humaira, Nabila (Universitas Islam Malang, 2025)
This paper aims to explore my experience as an English teacher and an English learner who is struggling to improve English proficiency in spoken and written communication. This study uses an autoethnographic approach to reconstruct barriers in learning English as well as how the English language helped the researcher to grow better as a teacher candidate. I present my teaching journey experience as pieces of information for this investigation. My teaching journey at various levels of education and in different conditions has formed a new self-identity in viewing and learning, which contributes to my English language skills. The study highlights three key findings: (1) self-awareness of English proficiency development, which examines my evolving understanding of my linguistic strengths and weaknesses; (2) experiential learning through teaching practices, which demonstrates how the act of teaching fosters deeper language acquisition; and (3) critical turning points in English language acquisition, which identifies pivotal moments that significantly influenced the progress of acquiring the language. The implication of this study emphasizes the importance of experiential learning and reflective teaching practices for English language educators. Limitations and suggestions are also addressed in this study.